OP0277 Effect of Disease Modifying Drugs on Bone Mineral Density in Patients with Rheumatoid Arthritis, Psoriatic Arthritis, Psoriasis, and Ankylosing Spondylitis: A Meta-Analysis. (10th June 2014) - Siu, S.; Haraoui, B.; Roubille, C.; Richer, V.; Starnino, T.; McCourt, C.; McFarlane, A.; Fleming, P.; Kraft, J.; Lynde, C.; Gulliver, W.; Keeling, S.; et al.
Abstract : Background: Inflammatory arthritis is a risk factor for osteoporosis and it may be that treating systemic inflammation can improve bone mineral density (BMD). Objectives: The aim of this study was to examine if DMARDs, steroids, and biologic therapies for rheumatoid arthritis (RA), psoriatic arthritis (PsA), psoriasis (PSO), and ankylosing spondylitis (AS) affect BMD. The aim of this study was to examine if DMARDs, steroids, and biologics for rheumatoid arthritis (RA), psoriatic arthritis (PsA), psoriasis (PSO), and ankylosing spondylitis (AS) affect BMD. Methods: Medline, Embase, and Cochrane were searched from 1960 to present using English randomised controlled trials in adults. Review articles were excluded. Studies were grouped based on disease, treatment type, and site of BMD measurement (wrist, lumbar spine (LS), hip). ΔBMD were reported as standardized mean difference. Results: 393 studies were identified; 13 were eligible (11 RA, 0 PsA, 0 PSO, 2 AS). For RA, significantly less wrist bone loss was seen with biologics (ΔBMD =0.27SD, 95% CI 0.07-0.47, P=0.009, I 2 =0%) and corticosteroids (ΔBMD =0.54SD, 95% CI 0.23-0.85, P=0<0.001, I 2 =0%). Biologics had no significant effect on LS and hip BMD. Corticosteroids had more bone loss compared to placebo on LS (ΔBMD = -0.25SD, 95% CI -0.42 to -0.08, P=0.003, I 2 =52%) but no difference for hip. For AS, significant BMD increase was seen with biologics in both LS (ΔBMD = 0.98SD, 95% CI 0.73-1.23, P<0.001, I 2 =16%) and hip (ΔBMD = 0.38SD, 95% CI 0.14-0.63, P=0.002, I 2 =0%). PsA and PSO could not be analyzed due to no suitable RCTs. Conclusions: Based on our RA analysis, biologics and steroids were associated with less wrist bone loss (where synovitis is often present) but had no effect on BMD at the hip. Corticosteroids were associated with more bone loss in LS whereas biologics had no effect on BMD at the LS. For AS, biologics were associated with increase in both LS and hip BMD. Disclosure of Interest: S. Siu Grant/research support: This study was supported by an unrestricted grant from AbbVie. B. Haraoui Grant/research support: This study was supported by an unrestricted grant from AbbVie. Other grant support from Abbvie, Amgen, BMS, Celgene, Janssen, Pfizer, Roche, UCB. Consultant for: Abbvie, Amgen, BMS, Celgene, Janssen, Pfizer, Roche, UCB. C. Roubille Grant/research support: This study was supported by an unrestricted grant from AbbVie. Fellowship grants/bursary from the Foundation of the University of Montreal Hospital Center (CHUM). V. Richer Grant/research support: This study was supported by an unrestricted grant from AbbVie. T. Starnino Grant/research support: This study was supported by an unrestricted grant from AbbVie. C. McCourt Grant/research support: This study was supported by an unrestricted grant from AbbVie. Salary for the fellowship in Vancouver was funded by a Fellowship from Janssen-Ortho Canada and the British Association of Dermatology. A. McFarlane Grant/research support: This study was supported by an unrestricted grant from AbbVie. P. Fleming Grant/research support: This study was supported by an unrestricted grant from AbbVie. J. Kraft Grant/research support: This study was supported by an unrestricted grant from AbbVie. Investigator support from Abbvie, Amgen, Galderma, Janssen, Novartis. Consultant for: Abbvie, Amgen, Galderma, Janssen, Novartis, Leo. Speakers bureau: Abbvie, Amgen, Galderma, Janssen, Leo. C. Lynde Grant/research support: This study was supported by an unrestricted grant from AbbVie. Investigator support: Abbvie, Amgen, Celgene, Janssen-Ortho, Novartis, Eli Lilly, Merck, Leo Pharma. Consultant for: Abbvie, Amgen, Celgene, Janssen-Ortho, Novartis, Eli Lilly, Merck, Leo Pharma. Speakers bureau: Abbvie, Amgen, Celgene, Janssen-Ortho, Novartis, Eli Lilly, Merck, Leo Pharma. W. Gulliver Grant/research support: This study was supported by an unrestricted grant from AbbVie. Abbott/AbbVie, Actelion, Amgen, Astellas, Bio-K, Celgene, Galderma, Janssen, LEO Pharma, Merck/Schering, Novartis, Pfizer, Roche and Valeant. Consultant for: Abbott/AbbVie, Actelion, Amgen, Astellas, Bio-K, Celgene, Galderma, Janssen, LEO Pharma, Merck/Schering, Novartis, Pfizer, Roche and Valeant. Speakers bureau: Abbott/AbbVie, Actelion, Amgen, Astellas, Bio-K, Celgene, Galderma, Janssen, LEO Pharma, Merck/Schering, Novartis, Pfizer, Roche and Valeant. S. Keeling Grant/research support: This study was supported by an unrestricted grant from AbbVie. Unrestricted educational funding received from the following:Pfizer, Janssen, Astrazeneca, Roche; Participated in advisory boards as consultant for:Janssen, AbbVie, Roche, Amgen. J. Dutz Grant/research support: This study was supported by an unrestricted grant from AbbVie. Other research support Abbvie, Centocor, Janssen- Ortho, Novartis, ONO Pharmaceuticals, Roche. Consultant for: Janssen–Ortho, AbbVie Amgen, Leo, Roche. Speakers bureau: Janssen-Ortho, AbbVie Amgen, Leo. L. Bessette Grant/research support: This study was supported by an unrestricted grant from AbbVie. Other research support AbbVie, UCB, Janssen, and Amgen. Consultant for: AbbVie, UCB, Janssen, and Amgen. Speakers bureau: AbbVie, UCB, Janssen, and Amgen. R. Bissonnette Grant/research support: This study was supported by an unrestricted grant from AbbVie. Resdearch grnats and honoraria AbbVie, Amgen, Celgene, Eli-Lilly Galderma, Incyte, Janssen, Leo Pharma, Merck, Novartis, Pfizer, Tribute. Consultant for: AbbVie, Amgen, Celgene, Eli-Lilly Galderma, Incyte, Janssen, Leo Pharma, Merck, Novartis, Pfizer, Tribute. J. Pope Grant/research support: This study was supported by an unrestricted grant from AbbVie. AbbVie, Actelion, Amgen, Astra Zeneca, Bayer, BMS, Celgene, Genentech, GSK, BMS, Jansen & Jansen, MedImmune, Mediquest, Novartis, Pfizer, Roche, United Chemicals Belgium, Consultant for: AbbVie, Actelion, Amgen, Astra Zeneca, Bayer, BMS, Celgene, Genentech, GSK, BMS, Jansen & Jansen, MedImmune, Mediquest, Novartis, Pfizer, Roche, United Chemicals Belgium DOI: 10.1136/annrheumdis-2014-eular.2540